2020
DOI: 10.3390/math8071176
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Inference for the Multicomponent System Based on Progressively Type II Censored Samples from Generalized Pareto Distributions

Abstract: In this paper, the reliability of a k-component system, in which all components are subject to common stress, is considered. The multicomponent system will continue to survive if at least s out of k components’ strength exceed the common stress. The system reliability is investigated by utilizing the maximum likelihood estimator based on progressively type II censored samples from generalized Pareto distributions. The confidence interval of the system reliability can be obtained by using asymptotic normality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The s-out-of-k G system has attracted extensive attention and R s,k inference has been broadly investigated by numerous studies. These include multicomponent strength-stress models for Kumaraswamy distribution by Dey et al [7], based on Chen distribution by Kayal [8], based on general class of inverse exponentiated distribution and proportional reversed hazard rate distribution by Kizilaslan [9,10], based on bivariate Kumaraswamy distribution by Kizilaslan and Nadar [11], based on Marshall-Olkin bivariate Weibull distribution by Nadar and Kizilaslan [12], based on Rayleigh stress-strength model by Rao [13], based on Burr XII distribution by Rao et al [14], based on progressively Type-II censored samples from generalized Pareto distribution by Sauer et al [15], and based on Rayleigh stress-strength model by Wang et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…The s-out-of-k G system has attracted extensive attention and R s,k inference has been broadly investigated by numerous studies. These include multicomponent strength-stress models for Kumaraswamy distribution by Dey et al [7], based on Chen distribution by Kayal [8], based on general class of inverse exponentiated distribution and proportional reversed hazard rate distribution by Kizilaslan [9,10], based on bivariate Kumaraswamy distribution by Kizilaslan and Nadar [11], based on Marshall-Olkin bivariate Weibull distribution by Nadar and Kizilaslan [12], based on Rayleigh stress-strength model by Rao [13], based on Burr XII distribution by Rao et al [14], based on progressively Type-II censored samples from generalized Pareto distribution by Sauer et al [15], and based on Rayleigh stress-strength model by Wang et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Mahato et al [22] studied the reliability of the mentioned system under progressive Type II monitoring data when the failure times fol-low Inverted exponentiated Distribution. Sauer et al, in 2020 [23]. As well, Rasekhi et al in 2020 [24], Mezaal et al in 2020 [25], Lately in 2021, Kohansal and Shoaee in [26], reported the reliability of the system using the Weibull Distribution.…”
Section: Introductionmentioning
confidence: 96%
“…This censoring is widely adopted by scholars due to its more efficient and flexible performance: testers can remove units from the experiment whenever needed and whenever failures occurred. Balakrishnan (2007), Wang et al (2014), Chaudhary and Tomer (2018), Almetwaly and Almongy (2018), Sauer et al (2020), Lone et al (2021a) and Dutta and Kayal (2022). Further, comparative lifetime experiments model is of great importance in reliability study, because it reduces the cost and accelerates the testing time.…”
Section: Introductionmentioning
confidence: 99%